Studies of Quaternary deformation zones through geomorphic and geophysical evidence. A case in the Precordillera Sur, Central Andes of Argentina - Terrizzano, Carla Marina (2010)
At the northern sector of the Precordillera Sur (31° 50′-32° 40′ SL/68° 45′-69° 20′ WL), Central Andes of Argentina, NW-trending sinistral transpressive shear zones at different scales, product of the Late Cenozoic Andean deformation, are recognized. The most significant of them is the 120. km long Barreal-Las Peñas Belt and within it, a small-scale (7. km long) Quaternary sinistral transpressive shear zone, called Los Avestruces, has been detected from geomorphological and geophysical analysis (32° SL/69° 21 WL). Geophysical techniques were applied to better characterize the shallow structure and kinematics of some representative structures in this shear zone. In particular, the use of tomography of electrical resistivity methods allowed characterizing the subsurface geometry of some areas of interest, enabling the recognition of Quaternary layers against their original slope, the geometry of the reverse fault which uplifted the Pleistocene deposits of one of the highs, the geometry of a likely previous extensional fault reactivated and inverted during the Quaternary as well as the presence of a reverse blind fault, which has uplifted the Quaternary deposits of the Los Avestruces bog.The location of the above mentioned shear zones coincides with the northern branch of the NW-trending extensional Triassic Cuyana basin. Thus, their presence appears to be related to Andean reactivation of older (Triassic), mainly NW-trending, structures. In the northern area of the Precordillera Sur, as well as in other places of the world here discussed, these kinds of paleotectonic oblique features play a major role in defining the geometry and kinematics of Late Cenozoic deformation.